PETA PROBABILITAS LIKUIFAKSI KAWASAN LEMPUING KOTA BENGKULU BERDASARKAN DATA UJI SONDIR - Rena Misliniyati; Makmun R. Razali; Samsul Bahri (Inersia: Jurnal Teknik Sipil, 2019)
As one of the cities on the west coast of Sumatra Island is located in an active seismic lines, causing Bengkulu city into an area that has the potential for an earthquake. This allows also the potential danger of liquefaction when the earthquake occurred. One of the areas in Bengkulu city is the pathway through which the village Lempuing. This study aimed to analyze the potential for liquefaction at the Village Lempuing using probabilistic methods simplified procedure. Probability model used is the probability model developed by Haldar and Tang (1979). The data collected from the results of the geotechnical investigation sondir 6 point spread in the Village Lempuing. Soil resistance parameters in this analysis are based on test data sondir or Cone Penetration Test (CPT). Shear wave velocity data obtained from the correlation of the data CPT Vs. Seismic load parameters used were obtained from the Indonesian Earthquake Zoning Map of 2010 and the seismic history of the city of Bengkulu. The analysis shows the level of probability of liquefaction hazards at the study site is close to 100%. This suggests that the study site has great potential for liquefaction hazards occur when an earthquake occurs.